2017
DOI: 10.3758/s13423-017-1298-4
|View full text |Cite
|
Sign up to set email alerts
|

A dual memory theory of the testing effect

Abstract: A new theoretical framework for the testing effect-the finding that retrieval practice is usually more effective for learning than are other strategies-is proposed, the empirically supported tenet of which is that separate memories form as a consequence of study and test events. A simplest case quantitative model is derived from that framework for the case of cued recall. With no free parameters, that model predicts both proportion correct in the test condition and the magnitude of the testing effect across 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 106 publications
(130 reference statements)
10
70
1
Order By: Relevance
“…This paradigm thus compares the effects of cued recall tests versus restudying on memory. The testing effect for cued recall is robust; in their theoretical review, Rickard and Pan (2017) found that 96% of 114 experiments exhibited testenhanced learning on the final test.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This paradigm thus compares the effects of cued recall tests versus restudying on memory. The testing effect for cued recall is robust; in their theoretical review, Rickard and Pan (2017) found that 96% of 114 experiments exhibited testenhanced learning on the final test.…”
mentioning
confidence: 99%
“…Specifically, their data suggest that test memory in that case is functionally an inclusive-OR gate, such that the memory can be accessed on a later final test only if the originally presented cues, or a proper subset of them, are represented and the required response is the same. Introduction of the hypothesized inclusive-OR gate into Rickard and Pan's (2017) dual-memory model of the testing effect (wherein study and test events are assumed to create separate episodic memories) allowed that model to capture not only the general learning specificity effect but also the finding over multiple experiments of equivalent performance in the tested-different and restudy conditions (e.g., the results shown in Fig. 2).…”
mentioning
confidence: 99%
“…gives rise to a number of subsequent research questions, the most obvious of which concern what exactly happens in students’ brains when they are tested on material and how repeated testing enhances higher‐order cognitive skills other than mere recall. Recently, the set of mechanisms potentially underlying the direct testing effect was complemented by a ‘dual memory’ theory which proposes that restudying and retesting events form separate memories . If this holds true, it would be interesting to investigate the structure of the information that is being stored using TEL as it appears to allow for application of knowledge rather than just reproduction of facts.…”
mentioning
confidence: 99%
“…Ultimately, repeated retrieval may produce decontextualisation "wherein items become more retrievable but are no longer only associated with a specific context (e.g., the original study context)" (Lehman et al, 2014, p. 259; cf. also the dual memory theory, Rickard & Pan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, keyword mediators might eventually not be needed anymore when form-meaning associations become increasingly decontextualised and independent of the original encoding context (i.e., the keyword). A compatible theory from the retrieval practice literature, the dual memory theory (Rickard & Pan, 2018), proposes that while learners initially form a study memory during the encoding of items, retrieval practice leads to a second type of memory, test memory, which critically involves the formation of an association from the cue (e.g., foreign word) to the response (e.g., translation). The dual memory theory explains the shift from initially keywordmediated retrieval to direct retrieval with the idea that test memory becomes the primary route for retrieval after multiple retrieval events (Rickard & Pan, 2018).…”
Section: From Mediated To Direct Word Retrievalmentioning
confidence: 99%